원(圓)의 상징이 담긴 한국 고유자산의 정보디자인 관점 분석 - 김건동; Kim Geon Dong (기초조형학연구, 2017)
정보디자인은 서구에서 형성된 것으로 역사 사례 및 그의 해석이 주로 서구 문화중심이다. 하지만 정보디자인은 보편적 학문으로 서구 문화 외에도 전 세계 어느 곳에나 다양한 사례를 볼 수 있다. 우리나라도 의궤 등 우수한 기록 문화와 함께 정보디자인 관점으로 해석할 수 있는 여러 유형의 고유자산 자료들을 보유하고 있다. 하지만 관련 연구들이 역사학 등 인문학 연구로 국한되어 정보디자인 관점에서 연계 연구되지 못한 것이 현실이다. 따라서 본 연구는 정보디자인의 시각으로 우리의 고유자산을 분석하고자 하며, 그 중 우리의 사상과 정서가 깃들어 있는 원(圓)의 상징이 담긴 한국고유자산을 정보디자인관점으로 분석해 보는데 목적이 있다. 본 연구는 문헌과 선행연구를 통해 원과 정보디자인의 이론적 고찰을 한 후 사례분석을 위한 분석대상과 분석요소를 도출하였다. 분석대상인 고유자산 사례는 태극, 강강술래, 농악놀이로 선정하였으며, 분석요소는 정보의 일반적 내용, 정보의 상징적 의미, 정보의 시각화 측면으로 구분하여 대상 사례를 분석하였다. 본 연구를 통해 원(圓)의 상징이 담긴 한국고유자산의 경우 정보의 일반적 측면에서는 만물의 생성과, 창조에 해당하는 우주의 원리가 연결되어 있음을 발견할 수 있었다. 상징적 측면은 음양오행론 및 삼재론(천,지,인)과 연결되어 있음을 발견할 수 있었고 시각화 측면에서는 조용함과 움직임을 함께 담은 순환운동을 이루고 있었다. 마지막으로 각 분석내용을 정보디자인 관점의 적용방안으로 제시해보았다. Information design is formed in the West, and it`s historical examples and interpretation are mainly based on western culture. However, information design is a universal discipline, and there are various examples from all over the world. Korea also has many types of unique asset data that can be interpreted from an information design point of view along with an excellent record culture such as the Korean Uigwe : The Royal Protocols of the Joseon Dynasty. However, it is a current state that related researches are limited to the study of humanities such as history. So it has not been studied in connection with information design. Therefore, this study aims to analyze our unique assets from the point of view of information design, and to analyze the unique property of Korea which contains the symbol of circle embodying our thoughts and emotions from the information design perspective. In this study, the analysis of the target and element was derived for the case study after analyzing the theoretical and theoretical aspects of circle and information design through literature and previous research, This study analyzed the cases of Taegeuk, Kangangsullae, and Nongakgak, which are the subject of analysis, and analyze the contents by analyzing the general contents of information, symbolic meaning of information, visualization of information. Through this study, it can be found that in the case of Korea `s unique assets, which contain symbols of circles, the generality of information is connected with the creation of all things and the principle of universes corresponding to creation. The symbolic aspect was found to be connected with the Yin-Yang and the heaven, earth and man in asia. In the aspect of visualization, it was a circular movement containing both quietness and movement. Finally, this study presented each analysis as an application of information design perspective.